KARAKTERISASI BIOPLASTIK DARI PATI KULIT SINGKONG DENGAN PENAMBAHAN KITOSAN - Selvie Diana; - Adriana; - Saifuddin; Rijalul Fikri (Jurnal Teknologi, 2014)
Bioplastics is one of solutions of environmental problems. Fairly high starch content allows peel of cassava can be utilized as a plastic film that can be described biodegradation by microorganisms naturally back into compounds that are environmentally friendly. This study aimed to determine the effect of chitosan on the characteristics of bioplastics made from cassava starch peel. This research was conducted in three phases, namely cassava starch manufacture peel, manufacture of bioplastics from starch cassava peel and analysis stages that include tensile strength test (Tensile Srength), swelling test, biodegradation test and a test of functional groups using FTIR. The results showed that chitosan is able to improve the mechanical properties of bioplastics and water resistance properties. This is indicated by the value of 6.67 MPa tensile strenght and swelling test by 60% generated by the composition of peel cassava starch 12 grams, chitosan 3% and 4 ml glycerol plasticizer. While microbial biodegradation test by using EM4 shows that bioplastics can be degraded for 6 days. Results of the analysis indicate functional groups bioplastics from cassava starch showed a pattern peel absorption at wave number region similar to cassava starch peel where there is CH, C = C and OH